PEMBERIAN SANKSI ATAS PELANGGARAN UNDANG-UNDANG PERKAWINAN DI NEGARA- NEGARA ISLAM: - M Atho Mudzhar (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2014)
This paper attempts to compare the content of Marital Act in some Muslim countries today regarding both sanctions implemented against those who break the rules (fine, jail, or other sanctions). Comparative perspective is important to understand similarities and differences in the implementation of Islamic law in Indonesia and other Muslim countries. Additionally, it is also important to know on to what extent Indonesia has developed Islamic law on Marital Act in comparison to other Muslim countries. This kind of study is relatively scarce due to the limited sources and references. Six countries are investigated in this paper, including Egypt, Tunisia, Jordan, Iraq, Pakistan, and Malaysia.